Visualization analysis of the impact of corporate social responsibility on corporate competitiveness based on Citespace - Dongrui, Xu; Johar, Md Gapar Md; Tham, Jacquline (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of the study is to analyze research hotspots and trends regarding the impact of corporate social responsibility (CSR) on competitiveness, and to suggest recommendations for businesses and governments. The methodology of the study employs Citespace software to analyze articles related to "corporate social responsibility" and "corporate competitiveness" indexed in the Web of Science Core Collection from 2002 to June 2024, focusing on keyword co-occurrence analysis, keyword clustering, keyword bursts, timeline mapping, and author mapping. The findings indicate that the most frequent keywords are corporate social responsibility, performance, impact, financial performance, and management. Keyword clustering includes competitiveness, market share, corporate social responsibility, environmental management, sustainable development, and green innovation. The strongest keyword burst is environmental management, followed by business ethics, competitiveness, dynamic capability, and implementation. In terms of the timeline view, the research focus in this field was on image, reputation, and loyalty from 2015 to 2020. In this study, the authors with the highest number of publications were Isabel Sanchez-Hernandez, M., and Popescu, Cristina Raluca Gh., each publishing 4 papers. The conclusions indicate that scholars focus on aspects of customer trust and loyalty, brand image, corporate reputation, and green innovation to study CSR regarding research hotspots; the focus of CSR is the integration of stakeholder needs in CSR practices, and the focus of competitiveness is long-term indicators. The practical implications suggest that businesses can enhance their competitiveness by fulfilling social responsibilities and that governments can promote sustainable development policies.